Pengaruh Gagasan Double Movement Fazlur Rahman dalam Pembaharuan Pendidikan Islam - Nur Azizah Riska Ayu Astiani Mahmudah (Jurnal Studi Pendidikan Agama Islam, 2025)
Rapid advancements in information technology, the forces of globalisation, and dynamic social changes require Islamic education to continuously adapt in order to remain relevant to the demands of the modern era. One of the most significant challenges faced is the tendency towards a textualist understanding of religion that pays insufficient attention to context, resulting in the ethical values embedded in the Qur’an not being fully internalised by students. In this context, the concept of Double Movement introduced by Fazlur Rahman emerges as an important approach for renewing ways of thinking within Islamic education. This concept emphasises two stages in interpreting the Qur’an: first, understanding the Qur’an within its historical context at the time of revelation in order to identify universal moral principles; and second, reapplying these principles within contemporary social contexts.This study aims to examine Fazlur Rahman’s concept of Double Movement and to analyse its impact on the renewal of Islamic educational thought, particularly in relation to educational paradigms, educational objectives, curriculum development, and teaching methods. The research employs a qualitative approach with descriptive analysis through a library-based study. Data were obtained from primary sources, namely Fazlur Rahman’s works, as well as secondary sources including academic journals and relevant scholarly literature.The findings indicate that the Double Movement concept makes a significant contribution to the development of Islamic education that is more contextual, ethical, and responsive to the challenges of changing times. This approach encourages Islamic education to move beyond a sole focus on textual understanding of religious teachings towards the formation of character, moral awareness, and students’ critical thinking abilities. Thus, Fazlur Rahman’s ideas provide a strong conceptual foundation for the development of a transformative Islamic education that remains relevant to contemporary social realities.